Problem identification using root cause analysis for the development of college damage complaint system / Siti Masliza Khalid - Khalid, Siti Masliza (2017)
For my final year project, I did a development of system which the system known as College Damage Complaint System for Institut Kemahiran Mara Jasin (IKM Jasin). Currently, IKM Jasin still do not have any computerized system and still using manual approach to make complaint about college damage facilities and manage the complaint. The problem had been faces by institute are time limitation, availability of warden and data loss. Therefore, college damage complaint system was develop for overcome the issues. Before the system have been developed, the requirement will first be gathered and analyze using Root Cause Analysis technique. It is a technique that will be used to identify the root of the problem. It is also a technique that useful to understanding and solving the problem. The most suitable methodology used is waterfall model which is System Development Life Cycle (SDLC) models because the methodology more ease to understand by development either the developer is professional developer or beginner developer. The process of the methodology also more easy to understand. To ensure this project running smoothly, an interview was conducted with college admin of IKM Jasin, Puan Alia bt. Ramli to gather and analyse the requirement that needed in the implementation of the system. A survey also has been conducted with the student at IKM Jasin to get the requirement for the analysis to identify the problem. For future work, this system will be enhance according the growth of the technology and will keep on updated.